2020
DOI: 10.1016/j.anr.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Body Image Changes in Chinese Patients Living with Inflammatory Bowel Disease: A Descriptive Qualitative Study

Abstract: Body image changes are common among patients living with inflammatory bowel disease (IBD) because of the illness and related treatments. Currently, there is little known about how those patients experience and perceive their altered body image in the literature. The aim of this study was to explore the experiences of body image changes in patients with IBD in China and to describe how those changes influence patients' perception of body and self. Methods: This study used a descriptive qualitative approach. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…However, I could not tell the truth." [67] There was a palpable sense of relief when people were able to overcome this struggle and not only share their true experiences but be their true selves. Being authentic was liberating and empowering.…”
Section: The Freedom Of Authenticitymentioning
confidence: 99%
“…However, I could not tell the truth." [67] There was a palpable sense of relief when people were able to overcome this struggle and not only share their true experiences but be their true selves. Being authentic was liberating and empowering.…”
Section: The Freedom Of Authenticitymentioning
confidence: 99%
“…This promoted the transformation of self-positioning from "victim" to "survivor" and led to the re-examination of inherent concepts and their original life. This comparison method has been described in previous studies of patients with Crohn's disease [22,49], indicating that the application of this method has a certain universality and effectiveness. When patients said, "I'm not the unluckiest", and had fewer complaints about the illness, it demonstrated improved acceptance of the illness with the achievement of self-reconciliation, to a certain extent.…”
Section: Discussionmentioning
confidence: 77%
“…A Canadian study [21] explored the positive changes experienced by patients with in ammatory bowel disease after diagnosis and generated the following ve themes based on the ndings: interpersonal relations, personal growth, valuing life, new life paths and spiritual growth. Similarly, studies in China [22,23] have found that some patients with Crohn's disease undergo posttraumatic growth, including the formation of stronger and closer relationships with others, living in the present, and reordering priorities. Together, the above research indicates that some patients with Crohn's disease experience posttraumatic growth.…”
Section: Introductionmentioning
confidence: 97%
“…Because youth place a high level of importance on their bodily appearance and physical attractiveness, these bodily changes can be difficult to process. Unsurprisingly, body image concerns have been raised in studies focusing on pediatric IBD experiences in varying countries and contexts (see Brydolf & Segesten, 1996;Daniel, 2002;Nicholas et al, 2007;Karwowski et al, 2009;Ruan et al, 2020). In some cases of chronic illness, such feelings can motivate extensive body projects to achieve a "normal" appearance (Balfe, 2009).…”
Section: Physical Changes and Body Imagementioning
confidence: 99%